A Sociolinguistic Study of the Types of Swear-Words used Karen’s Diner’s Servers in the Instagram Reels - Xaverius Juan Tanuwijaya; Jusuf Imam Ibrahim (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This study examines the types of swear-words and the social factors influencing their use by Karen’s Diner’s servers, utilizing Battistella (2005) categorization of swear-word types and Holmes (2013) theory of social factors. This study used a descriptive qualitative method to analyze Karen’s Diner’s servers’ utterances, collected from the company’s Instagram Reels posted between June 2023 and May 2024. Six swear-words were identified, with fuck and fucking being the most frequently used. The findings of this study shows that obscenity is the most frequently used type with no cases of profanity. Analysis of the social factors revealed that most swear-words uttered were used in personal topics and served affective functions, implying that the swearing was intended to express emotion dominant sub-variables and entertain customers. In conclusion, the use of swear-words by Karen’s Diner’s servers supports the restaurant marketing strategy, where taboo language is utilized to entertain and interact with customers.